(untitled) - Brown, Karen A. (New York, 2010)
Managing Projects: A Team-Based Approach was written for a wide range of stakeholders, including project managers, project team members, support personnel, functional mangers who provide resources for projects, project customers (and customer representatives), project sponsors, project subcontractors, and anyone who plays a role in the project delivery process. The need for project management is on the rise as product life cycles compress, demand for IT systems increases, and business takes on an increasingly global character. This book adds to the project management knowledge base in a way that fills an unmet need—it shows how teams can apply many of the standard project management tools, as well as several tools that are relatively new to the field. Managing Projects: A Team-Based Approach offers the academic rigor found in most textbooks along with the practical attributes often found more often in trade/professional publications.
Keywords: Quản lý dự án,Project management